2012
DOI: 10.5539/sar.v1n2p275
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Native Soap on Insect Pests and Grain Yield of Cowpea (Vigna unguiculata (L) Walp) in Asaba and Abraka during the Late Cropping Season in Delta State, Nigeria

Abstract: Studies were conducted to test the effectiveness of native soap against cowpea insect pests during the late cowpea cropping season in two agro-ecological zones-Asaba and Abraka, Delta State. Four major insect pests, namely the cowpea aphid, Aphis craccivora Koch, the legume flower bud thrips, Megalurothrips sjostedti Tryb, the legume pod borer, Maruca vitrata Fab and pod sucking bugs were studied. The experiment was made up of five treatments-1, 2 and 3 percent concentrations of native soap, cypermethrin (as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Moreover, some studies had a positive effect in controlling other insects. A study suggests that native soap is an effective bio-pesticide against cowpea insect pests [35].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some studies had a positive effect in controlling other insects. A study suggests that native soap is an effective bio-pesticide against cowpea insect pests [35].…”
Section: Discussionmentioning
confidence: 99%
“…In general, synthetic products have a higher insecticidal power compared to organic products [33]. Several authors [34,35] and [33], have reported the efficacy of cypermethrin on cowpea insect pests. However, the reduction in stem borers density in subplots treated with the aqueous extract of T. peruviana seeds at a concentration of 16.66 g/l, shows the depressant effect of these extracts on maize stem borers [36] in work on the effect of T. peruviana kernels and Mucuna pruriens plants on cassava root scales in the field.…”
Section: Discussionmentioning
confidence: 99%